Penyelesaian Tindak Pidana Dan Penerapan Sanksi Asusila Oleh Anak Di Bawah Umur Di Gorontalo - Alfian Sompie; Mohamad Rusdiyanto U Puluhulawa; Lisnawaty W. Badu (Universitas Sains dan Teknologi Komputer, 2024)
Cases of crimes involving children as perpetrators of crimes bring their own phenomena. Considering that children are individuals who are still emotionally unstable have become legal subjects, the handling of crime cases with child perpetrators needs special attention, starting from the Criminal Procedure Law applicable to children. The Code of Criminal Procedure of the child regulates in particular the obligations and rights acquired by the child. The handling of children as perpetrators of criminal acts from year to year has always drawn criticism from academics, practitioners and the public. This is more due to the culture that is maintained from generation to generation in the mindset of law enforcement in dealing with criminal offenders. Regarding the systematics or legal order that in fact discusses about children, the existence of child criminal law if a child is committing a criminal act while he is still relatively underage or not legally competent. Children commit immoral acts that are currently happening in Gorontalo. This case really happened and the way the punishment turned out to be very different from adults in general. Cases of crimes involving children as perpetrators of crimes bring their own phenomena. Considering that children are individuals who are still emotionally unstable have become legal subjects, the handling of crime cases with child perpetrators needs special attention, starting from the Criminal Procedure Law applicable to children. The Code of Criminal Procedure of the child regulates in particular the obligations and rights acquired by the child.